Granulomatous thyroiditis: an unexpected finding leading to the diagnosis of sarcoidosis - Vespasiani Gentilucci, U.; Picardi, A.; Manfrini, et al., S. (Acta Biomedica Atenei Parmensis, 2004)
A 59-year old male presented with dyspnoea, dull pain at the base of the neck, fever, and a history of severe recurrent coronary disease. In the past he had undergone two angioplasties, multiple stenting, and a triple aorto-coronary bypass. The patient also experienced a painful enlargement of the thyroid gland with bilateral multiple lymphoadenopathies and thyrotoxicosis. Thyroid histology revealed interstitial noncaseating granulomas that are typical of thyroid sarcoidosis. The finding of granulomas in the thyroid allowed us to interpret the clinical manifestations of our patient leading to the diagnosis of sarcoidosis. The patient was ultimately treated for sarcoidosis and after one year of specific therapy has completely recovered without recurrence of cardiac or respiratory symptoms up to date.